The impact of artificial intelligence on research and higher education in Morocco - Moukhliss, Ghizlane; Lahyani, Khalid; Diab, Ghizlane (Intelektual Pustaka Media Utama, 2024)
Artificial intelligence (AI) has revolutionized various fields, including research and higher education. Thanks to its innovative applications, it has changed traditional teaching methods. This article aims to explore the impact of AI on these domains in Moroccan universities, focusing on its transformative influence, benefits, challenges, and future prospects. By analyzing current literature, case studies, and expert opinions, we elucidate how AI has enhanced research methodologies, empowered educators and students, and fostered innovation in academia. In addition, we discuss ethical considerations and potential concerns associated with the increasing integration of AI. Finally, we highlight the future prospects and opportunities offered by AI for research and higher education in Morocco.